Detection and Molecular Characterization of Bovine Leukemia Virus in Egyptian Dairy Cattle - Hamada, Rania; Metwally, Samy; Polat, Meripet; Borjigin, Liushiqi; Ali, Alsagher O.; Abdel-Hady, A. A. A.; Mohamed, Adel E. A.; Wada, Satoshi; Aida, Yoko (Frontiers in Veterinary Science, 2020)
Bovine leukemia virus (BLV) causes enzootic bovine leukosis (EBL), the most common neoplastic disease in cattle worldwide. The first EBL outbreak in Egypt was reported in 1997. To date, there are few studies regarding BLV diagnosis using only serological detection and no studies investigating the distribution of BLV provirus, which is the retroviral genome integrated into the host genome, in Egypt. The genetic characteristics of Egyptian BLV strains are also unknown. Therefore, we aimed to detect BLV provirus and determine BLV genetic variability among dairy cattle in Egypt. We collected 270 blood samples of dairy cattle from 24 farms located in five provinces in Egypt. Out of the 270 samples, 58 (21.5%) were positive for BLV provirus. Phylogenetic analysis based on 50 420-bp sequences of the BLV env-gp51 gene demonstrated that Egyptian BLV isolates were clustered into genotype-1 and -4, among 11 genotypes detected worldwide. Furthermore, phylogenetic analysis and alignment of the 501-bp sequence of the env-gp51 gene revealed that at least six genetically different strains are present in Egypt. Genotype-1 isolates comprised four different strains (G1-a, G1-b, G1-c, and G1-d) and genotype-4 isolates included two different strains (G4-x and G4-y). Moreover, in one farm with 100% infection rate, we identified three isolates of G1-a strain, 35 isolates of G4-x strain, and two isolates of G4-y strain. Overall, this study provides the first report on molecular prevalence of BLV in Egypt and records the coexistence of BLV genotype-1 and -4 in Egyptian cattle.